Effect of theophylline on exercise performance in patients with severe chronic obstructive pulmonary disease. Issue 4 (April 1994) - Fink, G; Kaye, C; Sulkes, J; Gabbay, U; Spitzer, S A
Abstract : BACKGROUND--Theophylline is a well known bronchodilator which has been used for more than 50 years in the treatment of obstructive pulmonary diseases. In patients with severe chronic obstructive pulmonary disease whose cardiopulmonary performance is limited by their ventilatory capacity the administration of theophylline may improve exercise performance. METHODS--A randomised, placebo controlled, double blind, crossover trial was conducted in 22 patients with severe but stable disease. The patients (mean age 68 years) were studied before and after one month of placebo and one month of treatment with a sustained release preparation of theophylline administered orally. The theophylline dose was adjusted until a blood level above 55.5 mumol/l was achieved. The two treatments were administered in random order and separated by a two week washout period. After theophylline was administered for one month a mean level of 68.2 mumol/l was achieved. Pulmonary function tests, arterial blood gas measurements, maximal voluntary ventilation (MVV), and an incremental exercise test were performed before (baseline) and at the end of the first and second month of treatment. RESULTS--Pulmonary function tests showed no improvement in the flow parameters but showed an improvement in MVV after treatment with theophylline. Pulmonary gas exchange was improved after theophylline (resting arterial PO2 8.91 v 8.59 kPa, PCO2 5.38 v 5.56 kPa). The incremental exercise study showed improvement in maximal work rate (86.5 v 75.0 watts) and maximal ventilation (VEmax) (46.7 v 43.01/min). The dyspnoea index on maximal effort (VEmax/MVV), anaerobic threshold, and oxygen pulse remained unchanged. Resting and exercise heart rate were higher after theophylline. CONCLUSIONS--Theophylline improved cardiorespiratory performance in these patients with severe chronic obstructive pulmonary disease mainly by increasing the ventilatory capacity.